How wealth matters for social policy. (December 2021) - Marx, Ive; Nolan, Brian
This special issue looks at wealth in relation to social policy from a variety of perspectives. The articles all shed an innovative light on wealth in relation to a range of topics relevant for social policy researchers. This introduction provides an overview of the papers in this special issue and then highlights some of the gaps and shortcomings that remain. We conclude with some reflections on what this means for the future of social policy and research on it.